2013
DOI: 10.1007/s00405-012-2334-7
|View full text |Cite
|
Sign up to set email alerts
|

The Zuckerkandl tubercle: problematic or helpful in thyroid surgery?

Abstract: The Zuckerkandl tubercle is a residue from the embryological development of the thyroid gland. Although it is undeniably well known in surgery, this is not so among otolaryngologists. Our objective is to highlight the importance of the Zuckerkandl tubercle, as it has proven to be a reliable point of reference to locate the upper parathyroid, the lower thyroid artery and the recurrent nerve. In order to study the Zuckerkandl tubercle, we made a prospective analysis of the posterolateral border of the thyroid lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 14 publications
6
24
0
3
Order By: Relevance
“…The anatomic correlations of the ZT with the recurrent laryngeal nerve and the superior parathyroid gland were reported by Gilmour, 2 but this structure subsequently received little attention. Following the description of the ZT as a constant anatomic landmark of the recurrent laryngeal nerve and its classification into 4 grades according to its size, 3 the topographic anatomy of these structures and the grading of the ZT have been studied both in patients during surgery [4][5][6][7][8] and in cadavers. 9,10 ZT has mostly been defined as a pos-terior or lateral projection or a projection from the posterolateral border of the thyroid lobe in previous studies, but it was recently reported as a posteromedial projection in a normal anatomic position.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomic correlations of the ZT with the recurrent laryngeal nerve and the superior parathyroid gland were reported by Gilmour, 2 but this structure subsequently received little attention. Following the description of the ZT as a constant anatomic landmark of the recurrent laryngeal nerve and its classification into 4 grades according to its size, 3 the topographic anatomy of these structures and the grading of the ZT have been studied both in patients during surgery [4][5][6][7][8] and in cadavers. 9,10 ZT has mostly been defined as a pos-terior or lateral projection or a projection from the posterolateral border of the thyroid lobe in previous studies, but it was recently reported as a posteromedial projection in a normal anatomic position.…”
mentioning
confidence: 99%
“…11 Most ZTs extend into the tracheoesophageal groove or posterior to the esophagus. 8,11 Failing to remove the ZT in its entirety during total thyroidectomy may result in persistent unrelieved symptoms or recurrence 4,12,13 as well as persistent radioiodine uptake on radioactive iodine scans. 7 An enlarged ZT may increase pressure symptoms.…”
mentioning
confidence: 99%
“…The ZT of the right thyroid lobe was previously reported to be larger than that of the left lobe (Mehanna et al, 2014), but the sizes were similar in the present study. The incidence of the ZT has generally been reported as within the range 60-80% (Pelizzo et al, 1998;Hisham and Aina, 2000;Gauger et al, 2001;Yalç yn and Ozan, 2007;Kaisha et al, 2011;Sheahan and Murphy, 2011;Gil-Carcedo et al, 2013;Mehanna et al, 2014), though there is one report of a very low incidence of 7% (Page et al, 2009). The ZT was classified by Pelizzo et al (1998) into four grades according to its size, from 0 to III (larger than 1 cm), but with no indication as to whether "size" meant the length of the base or the height of the structure.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the length and height were Grade III in 82% and 17%, respectively, of fresh specimens, and in 71% and 9% of fixed specimens. The incidence of Grade III has been reported as approximately 14% (Pelizzo et al, 1998), 24% (Sheahan and Murphy, 2011), 37% (Yun et al, 2008), 45% (Gauger et al, 2001), 55% (Hisham and Aina, 2000), and 79% (Gil-Carcedo et al, 2013) in surgery-based studies, and 57% (Kaisha et al, 2011) in cadavers. This very wide range of incidences might be attributable to geographical or environmental factors, genetic or ethnic factors, or White-headed pins were stuck into the upper and lower margins of the ZT in the fresh specimen prior to fixation, and were used as reference markers for comparisons between the fresh and subsequently fixed specimens.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Traditionally cited factors contributing to difficulty in thyroid surgery include increased vascularity, inflammation, friability, fibrosis, and large gland size. [19][20][21] The thyroid surgery literature includes numerous examples of each individual item that comprises the Thyroidectomy Difficulty Scale.…”
Section: During the Late 19mentioning
confidence: 99%